Financial Management for UMKM at the RW Level Discussion Forum in Tangerang City - Namora, Afaf Boru Bulan; Sasmita, Djenni (Talenta Publisher, 2021)
The main objective of community service is to carry out financial management for MSMEs at RW level in Tangerang City. Micro, Small, and Medium Enterprises (MSMEs) are micro, small and medium enterprises which are one of the business sectors that still survived during the Indonesian economic crisis in 1998. These businesses can survive, because they do not depend on import trade or expect funding from banks. This financial management is carried out in a discussion forum at the RW level in the city of Tangerang to improve the welfare of the community in managing finances for micro businesses independently. The government realizes that financial management is one of the places for the community to empower and develop MSMEs. This service activity is carried out to manage finances in detail and properly managed at the RW level, Tangerang city. This implementation method consists of seminars and training. The results of the seminar and financial management training at the RW level discussion forum in the city of Tangerang went well because the participants received knowledge that was useful for training for the progress of their business. Based on the results of research carried out conducting umkm activities can improve detailed and correct financial management even though many people do not understand financial reporting in accounting, but because of the holding of seminars and training it has produced good results for the people of Tangerang city, thereby reducing unemployment.